Transboundary transportation of CO2 streams by ships: regulatory barriers for scaling up carbon capture and sub-seabed storage - Argüello, Gabriela; Bokareva, Olena (Frontiers in Marine Science, 2024)
Over the years, Carbon Capture and Sequestration (CCS) has been recognized as a crucial element in the toolkit of measures to combat climate change. At the European Union (EU) level, CCS plays a vital role in climate policy, particularly in reducing CO2 emissions from hard-to-abate industries. However, no comprehensive legal framework covers all stages of CCS. These stages include carbon capture techniques, transportation by ships or pipelines, injection, site closure, and post-closure management. Each of these stages is regulated by different legal frameworks that address various topics such as geoengineering, climate change, industrial activities, property, transportation, port operations, waste management, dumping, health, and the environment. Critical legal questions remain unanswered, such as who is liable for discharges in the marine environment during the transportation of CO2 by ships and for the long-term management of sub-seabed storage sites. As the transportation of CO2 by ships will likely have transboundary implications, we explore the legal possibilities, limitations and risks associated with exporting CO2 streams for sequestration under the sub-seabed.